2003
DOI: 10.1093/bja/aeg196
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of rectal acetaminophen and ibuprofen alone or in combination for paediatric day-case adenoidectomy †

Abstract: We conclude that prophylactically administered rectal acetaminophen combined with ibuprofen does not improve analgesia after adenoidectomy in the immediate postoperative period compared with either drug alone but does decrease the need for analgesia at home. Ibuprofen results in lesser sedation and faster discharge than when acetaminophen is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 28 publications
(7 reference statements)
2
57
0
11
Order By: Relevance
“…17 Those authors emphasized the importance of scheduling follow-up evaluations for combination therapy that extend beyond the immediate postoperative period. This may explain the finding of Viitanen et al that superiority of the combination was evident only following discharge from hospital 14 as well as our own result that a requirement for post-discharge rescue medication was eliminated for children receiving the combination. Mean Difference vs Combination (95% CI for difference) -0.9 (-6.2 to 4.5) -4.6 (-9.9 to 0.67)…”
Section: Limitationssupporting
confidence: 67%
See 3 more Smart Citations
“…17 Those authors emphasized the importance of scheduling follow-up evaluations for combination therapy that extend beyond the immediate postoperative period. This may explain the finding of Viitanen et al that superiority of the combination was evident only following discharge from hospital 14 as well as our own result that a requirement for post-discharge rescue medication was eliminated for children receiving the combination. Mean Difference vs Combination (95% CI for difference) -0.9 (-6.2 to 4.5) -4.6 (-9.9 to 0.67)…”
Section: Limitationssupporting
confidence: 67%
“…14 Results of all three studies showed the combination treatment to be superior to acetaminophen alone, although studies comparing the combination treatment with ibuprofen alone showed conflicting results. 14,16 These conclusions are inconsistent with our data showing no difference between the three treatments with regard to the primary outcome measure. Our secondary findings are more aligned with this previous work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oztekin et al also reported that pre-emptive rectal diclofenac reduced postoperative pain intensity and PCA morphine requirements of children anaesthetised with remifentanil for tonsillectomy [19]. Viitanen et al demonstrated that the total morphine used was significantly less in groups receiving paracetamol, ibuprofen or their combination compared to those receiving placebo for paediatric adenoidectomy, but the combination offered insignificant improvement in analgesia [20].…”
Section: Discussionmentioning
confidence: 99%